Marka DNA yang Dapat Digunakan untuk Konstruksi Peta Genetik dari Genom Jarak Pagar - Dani Satyawan; I Made Tasma (Jurnal Tanaman Industri dan Penyegar, 2011)
Jatropha (Jatropha curcas) is an oil producing crop that can be used as supplements or substitutes of diesel fuel to replace fosil-based energy. This crop has a relatively long life cycle, and therefore, a new alternative breeding method is necessary to expedate breeding program. The purpose of this study was to find out DNA marker technologies that can be used to map the genome of jatropha, and  later can be used to label the important agronomic characters of this plant. DNA markers tested in this study included Randomly Amplified Polymorphic DNA (RAPD), Amplified Fragment Length Polymorphism (AFLP), Target Region Amplification Polymorphism (TRAP), and Sequence Related Amplification Polymorphism (SRAP). Studies were initiated by finding the best method for isolating jatropha genomic DNA. Initial studies to obtain molecular markers applicable for this crop resulted in a total of 43 polymorphic RAPD bands that can be used for DNA fingerprinting studies as well as be useful for genetic mapping purposes. However, the number of markers available was extremely lower than the minimum target of at least 250 polymorphic markers necessary for a minimum coverage of the jatropha genome.  The remaining markers can be obtained from other marker methods such as AFLP, TRAP, and SRAP and based on this study the latter types of markers demonstrated more polymorphism level than that of RAPD.